SAFETY CLIMATE ANALYSIS FACTOR TO IMPROVE OCCUPATIONAL HEALTH AND SAFETY IN CONSTRUCTION WORK AT PT XYZ BUNYU FIELDWORK AREA - Zulfani Haki; Achmadi, Fuad; Vitasari, Prima (Lembaga Penelitian dan Pengabdian Masyarakat, Institut Teknologi Nasional (ITN) Malang, 2024)
The oil and gas industry is a workplace with many sources of danger, such as gas pressure, explosions, fire, electricity, moving equipment, and transportation. Field observations often result in work being stopped due to findings regarding unsafe conditions and unsafe actions in the workplace. Efforts can be made to protect workers' occupational health and safety by creating a safe climate in the workplace. This research aims to provide improvement solutions based on the safety climate factors that are most important in improving occupational health and safety in construction work. This research uses quantitative research methods. The research was conducted at the PT XYZ Bunyu fieldwork area in Bulungan Regency, North Kalimantan Province. The population used was all construction work employees under the supervision of the operation & surface facilities construction department, totalling 200 workers, while the sample was 180 workers. This research uses the Exploratory Factor Analysis method. The safety climate factor analysis results show that the total variance is 86.538%. Four factors were produced: training and compliance for occupational health and safety at 60.58%, leadership, knowledge, and attitude of workers at 15.392%, management commitment and worker initiative at 6.313%, and safety campaign at 4.248%. Implementing the proposed improvements uses one factor, a safety campaign, where observations indicate that field implementation has been carried out well. This research does not analyse the relationship between the influence of safety climate factors on occupational health and safety; the suggestions for further research include examining the relationship between the influence of safety climate factors on occupational health and safety to find out the technical aspects and to apply existing factors directly in the field.